Economic estimates of invasive wild pig damage to crops in 12 US states - McKee, Sophie; Anderson, Aaron; Carlisle, Keith; Shwiff, Stephanie A. (Crop protection, 2020)
We report the results of a survey on invasive wild pig (Sus scrofa L.) damage and control in 12 US states (Alabama, Arkansas, California, Florida, Georgia, Louisiana, Mississippi, Missouri, North Carolina, Oklahoma, South Carolina, and Texas). The crops chosen for this study represent the “second tier” in terms of economic importance after the six crops that were the subject of Anderson et al. (2016). The survey was distributed by the USDA National Agricultural Statistical Service (NASS) in the summer of 2019 to a sample of producers in each of the states (except California) of the following six crops: hay, pecans (Carya illinoinensis (Wangenh.) K.Koch), melons (cantaloupe (Cucumis melo L. var. cantalupensis), honeydew (Cucumis melo L. (Inodorus Group)), and watermelon (Citrullus Schrad.), sugarcane (Saccharum officinarum L.), sweet potatoes (Ipomoea batatas (L.) Lam.), and cotton (Gossypium L.). In California, where there the crops of economic importance differed from the other states in the study, damages were calculated for producers of hay, almonds (Prunus dulcis (Mill.) D.A. Webb), grapes (Vitis vinifera L.), sod, carrots (Daucus L.), lettuce (Lactuca L.), and strawberries (Fragaria L.). In total, 7438 respondents completed the questionnaire. Findings indicate that damage can be substantial. The highest yield loss estimates occurred for hay in Texas. Control efforts were common, but no control method was rated by the majority of producers as very effective. Extrapolating crop damage estimates to the state-level in 12 states with reportable damage yielded an estimated crop loss of $272 million/yr. Though large, this number likely represents only a small fraction of the total damage by wild pigs in these states because it only includes crop damage to six crops. We hope findings from this survey will help guide control efforts and research, as well as serve as a benchmark against which the effectiveness of future control efforts can be measured. •Estimated crop loss due to feral swine of $272 million for the surveyed set of crops in 12 states.•Highest loss ratio was reported for pecans (Texas 13.46% and Florida 12.56%).•Loss ratio for cotton was lower, ranging from 0% in Missouri to 3.1% in Florida.•No control method was rated as extremely effective by the majority of the respondents.